PTH-004 Subjective Description Of Pain Does Not Predict Biliary Manometry Or Response To Endotherapy In Sphincter Of Oddi Dysfunction: Are The Rome Criteria Fit For Purpose?. (9th June 2014) - Paranandi, B; Cheung, VTF; Joshi, D; El-Sayed, GH; Johnson, GJ; Pereira, SP; Webster, GJ; Chapman, MH
Abstract : Introduction: In the absence of biochemical or radiological evidence of biliary obstruction, Sphincter of Oddi dysfunction (SOD) is a difficult condition to diagnose and to treat. The Rome III diagnostic criteria clearly state that, to meet a diagnosis of SOD, a patient should have "episodic pain at different time intervals (not daily)". We observe heterogeneity in symptoms amongst patients referred with suspected SOD with many patients reporting constant daily pain requiring potent analgesia. We aim to determine whether subjective reporting of pain (according to the Rome criteria) correlates with Sphincter of Oddi Manometry (SOM: the gold standard for diagnosis of SOD) and/or response to endoscopic sphincterotomy/plasty (ES). Methods: An ERCP database and electronic clinic lists (from September 2011 to 2013) were analysed to identify all cases of suspected SOD. Patients underwent a telephone questionnaire based on subjective recall of pre-ERCP pain according to the Rome criteria and post-ERCP response. Patients were asked to categorise pain as either intermittent with no pattern/not daily (Rome +ve) or daily/constant pain (Rome –ve). Results: 163 new patients with suspected biliary SOD were identified of whom 89 underwent ERCP. They were mostly Female (87%), White British (86%) with median age 37 years (range 18–69). 48 patients with SOD2/3, who underwent SOM, agreed to answer the questionnaire. Patients with SOD1 do not routinely undergo SOM. Biliary and/or pancreatic basal pressures were abnormally elevated (>40 mmHg) in 33/37 (89%) SOD2 and 8/10 (80%) SOD3, all of whom underwent ES. There were no significant correlations between Rome +ve pain and either biliary manometry (p = 0.3) or improvement in pain following ES (p = 0.2) in patients with either SOD 2 or 3 (see tables). However, there was a high relapse rate after initial improvement across both groups (SOD2 17/26=65%, SOD3 2/7=29%) irrespective of whether patients had Rome +ve or –ve pain initially. Conclusion: Despite the clear recommendations of the Rome criteria requiring intermittent/episodic pain for a diagnosis of SOD, our data suggest that correlation between description of pain and biliary manometry is poor. 30–35% of patients who meet the current gold standards for diagnosis of SOD have constant or daily (Rome –ve) pain. Additionally, description of pain does not predict response to endotherapy suggesting that the Rome criteria and/or SOM for suspected SOD are not clinically useful and may need to be redefined. We note that high rates of positive SOM and recurrence of pain post-ES was seen in our cohort. Disclosure of Interest: None Declared.